MEMOIRS OF STATE ACTORS OF KARAKALPAKSTAN - T. Pirniyazova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article analyzes a large complex of memoirs of the statesmen of Karakalpakstan - Allayar Dosnazarov, Pirzhan Seitov, Nauryz Zhapakov and others. A tribute is paid to the memoirs of Uzbek statesmen. The importance of memoirs as a source in the study of the history of Karakalpakstan in 1917-1991 is noted. The key points of the modern history of Karakalpakstan are underlined, where the memoirs of the statesmen of Karakalpakstan could be used